The Influence of Community Participation and Destination Management on the Development of Sustainable Tourism at Pangumbahan Turtle Park - Cindy; Amtiar Hema Malini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Sustainable tourism development in conservation-based destinations depends on effective community participation and destination management; however, the relative contribution of these factors at Pangumbahan Turtle Park remains insufficiently understood. This study aimed to examine the effects of community participation and destination management on sustainable tourism development at Pangumbahan Turtle Park. A quantitative descriptive design was employed, involving 100 respondents comprising local community members, destination managers, and other tourism stakeholders selected through purposive sampling. Data were collected using questionnaires and analyzed with IBM SPSS Statistics Version 32 through validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, an F-test, and coefficient of determination analysis. The findings indicate that community participation had a positive and statistically significant effect on sustainable tourism development (t = 5.336, p < .001), whereas destination management did not demonstrate a significant partial effect (t = 1.260, p = .211). Simultaneously, community participation and destination management significantly influenced sustainable tourism development (F = 208.670, p < .001). The adjusted R² value of .808 indicates that the two predictors explained 80.8% of the variance in sustainable tourism development, while the remaining 19.2% was attributable to other factors. The study concludes that community participation is the dominant determinant of sustainable tourism development at Pangumbahan Turtle Park. These findings contribute empirical evidence to the sustainable tourism literature by clarifying the relative influence of participatory and managerial factors in a conservation-based destination. Practically, the results underscore the need to strengthen community involvement while improving destination management practices to support the long-term sustainability of conservation tourism.